Resgate, conservação e multiplicação da agrobiodiversidade crioula: um estudo de caso sobre a experiência dos guardiões das sementes crioulas de Ibarama (RS) - Kaufmann, Marielen Priscila (2014)
The municipality of Ibarama is located in the central mountain range of Rio Grande do Sul and about 70 % of it's population consists of family farmers. It stands out among the other municipalities by having a unique and innovative experience regarding the rescue, conservation and sustainable use of numerous native species and cultivars of agrobiodiversity, carried out by several of these families. The present work lead to the organization of the Native Seed Keepers Association of Ibarama (Associação dos Guardiões de Sementes Crioulas de Ibarama) and has become fundamental in the design of rural development strategies. Thus, this work aims to contribute to the socioeconomic characterization of the saving and multiplication experience of native maize (Zea mays) in the community. Semistructured interviews as well as participatory observations were conducted with 12 farmer families of Ibarama. Social structure features such as gender, age and family composition and their relation to the species preservation were analyzed, as well as the purposes and expectations of their production. The research shows that the preservation activities of native maize varieties are maintained through generations, due to subsistence production and economic, social, political and cultural elements that are directly related to its use as family food and animal feed. The farmers themselves have developed their own way of connecting with their natural surroundings and often use evidence or trial for perfecting the domestication of the plants and animals that they handle. It is also observed that farmers adapt and shape agrobiodiversity according to their own requirements and needs, which are influenced by ecological, social and economic changes. In regard to the continuation of the Association there are many limitations such as the age of the seed keepers and the lack of political incentive. Strategies to address these problems are the cooperation of the Association with research and teaching entities, and the group of little Guardians as well as the access to new marketing channels for native agrobiodiversity products, specifically those of native maize.